401 Do gender differences exist in the injury profile of collegiate gaelic footballers?. (3rd March 2020) - O'Connor, Siobhán; Calvin, Teahan; Whyte, Enda
Abstract : Background: Gaelic football is one of the most popular sports played by Irish male and female collegiate student-athletes. While one previous study examined injury incidence in male collegiate Gaelic footballers, no prospective published research exists in Ladies Gaelic footballers and no gender comparisons in the sport has yet been completed. Objective: To examine injury epidemiology in male and female collegiate Gaelic footballers. Design: Prospective epidemiological study Setting: Collegiate athletics in one Irish institution Patients (or Participants): Male (n=125) and female (n=82) collegiate Gaelic footballers. Interventions (or assessment of risk factors): Certified Athletic Therapists and student athletic therapists and trainers captured all injuries that led to a missed Gaelic football session over one collegiate season. Exposure in hours was recorded by student athletic therapists and trainers that attended all trainings and matches. Main outcome measurements: Injury proportion and total, match and training injuries per 1, 000 hours were calculated. Descriptive statistics were also measured. Results: A higher incidence proportion (69%) and match injury rate (44.27 per 1, 000 hours) was noted in male Gaelic footballers than females (39%, 24.75 per 1, 000 hours). A similar injury profile was observed between genders. Lower body injuries (77.9%, 81.3%) were most frequent in males and females respectively, particularly hamstring (27.3%, 28.0%), ankle (16.9%, 13.0%) and knee injuries (13.0%, 13.0%). Females displayed a greater mean days absent (39.9±47.2) compared to males (28.4±34.7) and a greater proportion of severe injuries (59.4% vs 42.9%). Knee (145.0 days lost per 1, 000 hours) and hamstring injuries (112.1 days lost per 1, 000 hours) led to the greatest injury burden. Conclusions: While injuries are more frequent in male collegiate players, injuries lead to a greater injury burden in females, highlighting the need for injury prevention prioritisation. A relatively similar injury profile exists between genders and so injury prevention strategies designed for males, such as the Gaelic Athletic Association 15+ injury prevention program (GAA15+), may be of use in female Gaelic footballers.